NILAI-NILAI FILOSOFIS DALAM UPACARA ADAT MONGUBINGO PADA MASYARAKAT SUKU GORONTALO - Moch Zihad Islami; Yulia Rosdiana Putri (JURNAL ILMU BUDAYA, 2020)
The research is regarding Mongubingo traditional ceremonies in a Gorontalo tribe. Mongubingo is a series of circumcision custom performed on a baby girl of Gorontalo tribe. This tradition persists although being criticized in terms of health, women’s empowerment and child protection. The research aims to find out the philosophical meanings and values of Mongubingo traditional ceremonies. The research expected to provide a comprehensive understanding of the whole society regarding Mongubingo traditional ceremonies. The method used is a qualitative-descriptive approach through literature review, observation, interview, and documentation. The result of research indicates that Mongubingo tradition is maintained by the Gorontalo society because of their strong understanding of religious values through their philosophy. Philosophical values of Mongubingo traditional ceremonies are as the manifestation of life and character of the girl. The philosophical values are the basis of their goal to control the morality and social-emotional of children in their development to adulthood, being a woman according to the custom, culture, and religion of the Gorontalo tribe.